Pyrene-based metallocycles and metallocages: more than fluorophores. (16th September 2020) - Wang, Xu-Qing; Ling, Qing-Hui; Wang, Wei; Xu, Lin
Abstract : This review comprehensively summarizes the construction of pyrene-based metallocycles and metallocages as well as their properties and applications. Abstract : Attributed to their synthetic accessibility, unique structural and intriguing photophysical features, pyrene moieties have recently been introduced into supramolecular coordination complexes (SCCs) such as metallocycles and metallocages as either functional groups or key panels. The resultant pyrene-based SCCs displayed not only attractive emission properties but also impressive binding abilities towards diverse guests, endowing them with wide applications in sensing, host–guest chemistry, light harvesting etc. In this review, a comprehensive summary of pyrene-based metallocycles and metallocages is presented, and the emphasis will be on the intriguing photophysical features and unique host–guest chemistry that the pyrene moieties bring to the SCCs.